Political Marketing Through New Media: A Comparison and Contrast of FDR’S Fireside Chats and Trump’s Tweets - Allen, Charlotte (Journal of Marketing Development and Competitiveness, 2020)
This paper contains both a comparison and contrast on the use of nontraditional media channels by a US president in order to communicate directly to the American population. Presidents Franklin Delano Roosevelt and Donald J. Trump have utilized the technology available in their respective time periods for the process of political disintermediation, side stepping the traditional news media to communicate directly with the American population.